Efeito do método Pilates sobre as variáveis hemodinâmicas e da creatina quinase em mulheres hipertensas - Santos, Juviane Menezes dos (2017)
Introduction: The hypertension is a systemic dysfunction that changes several terms metabolic conditions, among them: an increase in blond pressure, an increase in the enzymatic activity of creatine kinase. Physical exercise has been widely used in the control of these alterations the effect of the Pilates method on hemodynamic variables and creatine kinase in hypertension women. Objective: To evaluate the effect of the Pilates method on hemodynamic variables and creatine kinase in hypertensive women. Method: 30 hypertensive women (54.09 ± 5.71 years) and 15 normotensive women (49.5 ± 6.64 years) underwent 24 sessions of Pilates, twice a week with a duration of 60 minutes each session. They were measured before and after the end of each session, blood pressure and heart rate. For the CK analysis, blood collection was performed 72 hours before the start of physical training and 72 hours after the 24th session of Pilates. In the analysis of the data for comparison of the groups, two-way ANOVA was used for repeated measurements and the Student's t-test for non-paired samples. Results: There was no significant difference in blood pressure and heart rate for both groups (p> 0.05), however, in the CK analysis a significant difference was found between the group of hypertensive women (p = 0.0218).Conclusion: The method pilates did not interfered in the BP and HR of both groups, hoverer, it decrease in the level of creatine kinase in the group of hypertensive women.